2003
DOI: 10.1007/s00125-003-1178-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced activation of protein kinase C inhibits store-operated Ca 2+ uptake in rat retinal microvascular smooth muscle

Abstract: Aims/Hypothesis. To assess the effects of diabetes-induced activation of protein kinase C (PKC) on voltage-dependent and voltage-independent Ca 2+ influx pathways in retinal microvascular smooth muscle cells. Methods. Cytosolic Ca 2+ was estimated in freshly isolated rat retinal arterioles from streptozotocin-induced diabetic and non-diabetic rats using fura-2 microfluorimetry. Voltage-dependent Ca 2+ influx was tested by measuring rises in [Ca 2+ ] i with KCl (100 mmol/l) and store-operated Ca 2+ influx was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…Diabetes/HG effects on STIM1 expression/SOC function are cell context dependent (1,3,4,30,34,58). Like in platelets and vascular endothelial cells (4,58), prolonged HG treatment in MCs increased STIM1/Orai1 protein expression levels and augmented SOCE.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes/HG effects on STIM1 expression/SOC function are cell context dependent (1,3,4,30,34,58). Like in platelets and vascular endothelial cells (4,58), prolonged HG treatment in MCs increased STIM1/Orai1 protein expression levels and augmented SOCE.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in ROCK activity, enhanced production of diacylglycerols (DAG) and activation of PKC have all been shown to be associated with various vascular abnormalities, including arterial hypertension in DM (Inoguchi et al, 1992;Soloviev and Bershtein, 1992;Soloviev et al, 1998;Koya and King, 1998;Meier and King, 2000;Idris et al, 2001;Wettschureck and Offermanns, 2002;Curtis et al, 2003;Guo et al, 2003;Seko et al, 2003;Curtis and Scholfield, 2004;Ward et al, 2004;Salamanca and Khalil, 2005;Loirand et al, 2006;Das Evcimen and King, 2007). Taken together, these data suggest that the activation of ROCK and/or PKC may be causally linked to myofilaments Ca 2+ sensitization in the DM-associated hypertensive state.…”
Section: Introductionmentioning
confidence: 88%
“…Thus, both increased Ca 2+ influx and Ca 2+ release have been proposed to develop in DM and to account for the enhanced vascular reactivity. However, one controversy here is that voltage-and store-operated Ca 2+ entry channels can be, in fact, even inhibited in DM (Wang et al, 2000;Curtis et al, 2003). Alternatively, the Ca 2+ -sensitization of the contractile proteins has been proposed as a more general mechanism of elevated DM-associated vascular contractility.…”
Section: Introductionmentioning
confidence: 99%
“…[153][154][155][156] Curtis et al also proposed a PKCmediated pathway for the reduction of SOCE in the smooth muscle cells of retinal microvessels from STZ diabetic rats. 118 In their study, the PKC antagonist staurosporine completely restored the reduced SOCE in the diabetic vascular myocytes. 118 Further study suggested that the b isoform of PKC was responsible for the inhibition because PKCbII was specifically upregulated in diabetic retina, and an inhibitor of PKCb partially reversed the attenuated SOCE in the vascular smooth muscle cells from these diabetic rats.…”
Section: Protein Kinase Cmentioning
confidence: 90%
“…The attenuated SOCE was reversed by insulin treatment (to normalize blood glucose level). 118 Using the same diabetic model, Ma et al also found an attenuated SOCE in aortic smooth muscle cells of STZ rats. 119 Importantly, the contractile response of the vessel was significantly reduced in the diabetic rats compared to that in control rats.…”
mentioning
confidence: 90%